BLOODY CHRONICLES OF APRIL 9 - Landa Chokhelishvili; Tamar Ioramishvili; Nestan Kazarashvili; Gvantsa Machavariani; Madona Kebadze (Scholar Express Journal, 2022)
1989 year turned out crucial and one of the most important for Georgian national –liberation movement. When mentioning 1989, in the conciousness of society the first thing which is turned up is April 9 tragedy which took place in Tbilisi. This tragedy, which finally ended with victim, greatly hastened the dissolution process of Soviet Union and the restoration of Georgian Sovereignty
Keywords: crucial; important; Georgian; conciousness